The synergistic mechanisms of apo-ferritin structural transitions and Au(iii) ion transportation: molecular dynamics simulations with the Markov state model. Issue 32 (27th July 2021) - Peng, Xue; Lu, Chenlin; Liu, Zheng; Lu, Diannan
Abstract : Due to its unique structure, recent years have witnessed the use of apo-ferritin to accumulate various non-natural metal ions as a scaffold for nanomaterial synthesis. Abstract : Due to its unique structure, recent years have witnessed the use of apo-ferritin to accumulate various non-natural metal ions as a scaffold for nanomaterial synthesis. However, the transport mechanism of metal ions into the cavity of apo-ferritin is still unclear, limiting the rational design and controllable preparation of nanomaterials. Here, we conducted all-atom classical molecular dynamics (MD) simulations combined with Markov state models (MSMs) to explore the transportation behavior of Au(iii ) ions. We exhibited the complete transportation paths of Au(iii ) from solution into the apo-ferritin cage at the atomic level. We also revealed that the transportation of Au(iii ) ions is accompanied by coupled protein structural changes. It is shown that the 3-fold axis channel serves as the only entrance with the longest residence time of Au(iii ) ions. Besides, there are eight binding clusters and five 3-fold structural metastable states, which are important during Au(iii ) transportation. The conformational changes of His118, Asp127, and Glu130, acting as doors, were observed to highly correlate with the Au(iii ) ion's position. The MSM analysis and Potential Mean Force (PMF) calculation suggest a remarkable energy barrier near Glu130, making it the rate-limiting step of the whole process. The dominant transportation pathway is from cluster 3 in the 3-fold channel to the inner cavity to cluster 5 on the inner surface, and then to cluster 6. These findings provide inspiration and theoretical guidance for the further rational design and preparation of new nanomaterials using apo-ferritin.